PENGARUH TINGKAT SUKU BUNGA, DAN INFLASI TERHADAP INDEK HARGA SAHAM GABUNGAN (IHSG) PERIODE 2019-2024 - Alifal Salam; H Sayutin (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to determine whether interest rates and inflation have an effect on the Composite Stock Price Index (IHSG) on the Indonesia Stock Exchange for the period 2019–2024. The research method used is quantitative with an associative approach. The analysis in this study was conducted using SPSS Software Version 30. The analytical methods employed include validity tests, classical assumption tests, simple linear regression analysis, multiple linear regression analysis, coefficient of determination, partial t-test, and simultaneous F-test. The results show that: (1) partially, interest rates have a significant effect on the Composite Stock Price Index, as indicated by the t-test result where the t-value (3.234) is greater than the t-table value (1.99495), with a significance level of 0.002 < 0.05; (2) partially, inflation also has a significant effect on the Composite Stock Price Index, as shown by the t-value (2.340) being greater than the t-table value (1.99495), with a significance level of 0.022 < 0.05; and (3) simultaneously, interest rates and inflation have a positive and significant effect on the Composite Stock Price Index during the period 2019–2024, as indicated by the F-test result where the F-value (10.832) is greater than the F-table value (3.130). The coefficient of determination (R²) is 0.239, indicating that 23.9% of the variation in stock index performance is explained by the two independent variables, while the remaining 76.1% is influenced by other factors.